IMPLEMENTASI PROXY SERVER MENGGUNAKAN FITUR LAYER 7 PROTOCOLSMIKROTIK DI STMIK LOMBOK - Khalid, Syam Basri; Hairul Fahmi; M. Taufan Asri Zaen (Jurnal Elektronika Terapan dan Ilmu Komputer, 2025)
Abstract-Internet users, both Lecturers, Students and Staff of STMIK Lombok Campus, 75 - 85 % have accessed the internet, ranging from accessing social media, downloading games, watching videos to assignments from subject teachers. From the results of observations and interviews at the STMIK Lombok Praya campus, sites that are often accessed especially by STMIK Lombok Praya students are sites outside of learning content, such as Facebook, Youtube and several other game sites.Based on the SWOT analysis, taking into account internal and external factors of the ongoing network system, the researcher proposes a design and development of a new network configuration system by implementing a Layer 7 Protocols feature found on the Mikrotik RB750. The researcher explores the NDLC method in developing network systems, designing existing network systems and then adding routers and accesspoints as access media using wi-fi. The implementation of the layer 7 protocols feature has the ability to block the desired sites by writing several scripts in the menu contained therein. Management, monitoring and network management can be done at the same time by compressing the features of Mikrotik directly such as Filter rules, access lists.The results of Implementation of a Proxy Server with Layer 7 Protocols Mikrotik features on the STMIK Lombok Praya campus proved to be able to block desired sites such as facebook, youtube and online games, one of which is mobile legends games and other sites that use the https protocol. Besides that, the application of this proxy does not affect the speed or bandwidth of the internet connection at STMIK Lombok, Keywords: Proxy Server.Layer 7 Protocol